Contribution of watershed morphometry for groundwater conservation and advance of irrigated agriculture in the outcrop area of guarani aquifer system - Reissler, Joyce [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The basin morphometric analysis is the basis for understanding the natural physiographic conditions. The results provide susceptibility indicators to environmental degradation and assist in planning management and mitigating actions for the conservation and use of natural resources. The objective of this study was the morphometric characterization in an outcrop Guarani Aquifer System (GAS) area and to generate information for a better planning for groundwater resources conservation. The study area was Ribeirão do Jacú, Tejupá, SP, entirely in the outcrop area of GAS, a high vulnerability region with a tendency towards the advance of intensive irrigated agriculture. The Geographic Information System (GIS) was used for morphometric evaluation. The results indicated that there is lower surface runoff trend and greater soil infiltration capacity, which leads to greater care in land use and local management.
Contribuição da morfometria de bacias hidrográficas para a conservação das águas subterrâneas sob o avanço da agricultura irrigada em área de afloramento do sistema aquífero guarani
Keywords: Environmental planning; GAS; Groundwater